Cranial base chondrosarcoma: Clinicopathological analysis of a case - Romero Yauri, José (2021)
Introduction:Chondrosarcoma is an unusual malignant neoplasm; cranial location is rare. Sometimes its complete resection is not possible because of vicinity of the mass to important vascular and neural structures. Clinical case: This is a 56-year old female subject who developed headache in the right side, paresthesia in the right side of her upper lip, short term memory loss, and ageusia. A magnetic resonance imaging study showed an enhanced extra-axial mass. This patient underwent complete surgical resection. The anatomopathological study showed a well differentiated chondrosarcoma of the cranial base. Conclusion: Chondrosarcoma is a malignancy with pure differentiation of the hyaline cartilage. It represents 0.15% of all intracranial tumors, and this is the second case with a cranial base location reported in Peru. Both histological characteristics and immunohistochemistry markers revealed the classic characteristics of this tumor. Therapy is given on an individualized basis.